Illustration Graphic Design Training for Small Businesses as a Form of Business Development - Noor Laila Ramadhani; Ari Eko Budiyanto; Ahmad Ali (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the city of Magelang there is a wholesale Kedjora UMKM. These UMKM sell several fashion products, especially Muslim women's clothing which are self-produced and some buy from manufacturers in Bandung. In fact, they want the products they sell to be off the market, so they need skills to make their own designs. The problem is that the wholesale Kedjora UMKM has not been able to design clothes digitally so they buy more from producers in Bandung and Jakarta. Therefore the product is not exclusive. Based on the above it is important because if they can design their own products they will produce products that are not marketable and are able to compete in today's fashion industry. Through increasing skills in making digital clothing designs, those who already have the skills and want independent entrepreneurs who incidentally are on a small scale, they are able to compete with medium or large business actors in meeting the needs of individuals, organizations and the wider community in the global market.